Wrinkles - Manríquez, Juan Jorge (BMJ Publishing Group, 2008)
INTRODUCTION: Skin disorders associated with photodamage from ultraviolet light include wrinkles, hyperpigmentation, tactile roughness, and telangiectasia, and are more common in people with white compared with other skin types. Wrinkles are also associated with ageing, hormonal status, smoking, and intercurrent disease. METHODS AND OUTCOMES: We conducted a systematic review and aimed to answer the following clinical question: What are the effects of interventions to prevent and treat skin wrinkles? We searched: Medline, Embase, The Cochrane Library, and other important databases up to April 2008 (Clinical Evidence reviews are updated periodically; please check our website for the most up-to-date version of this review). We included harms alerts from relevant organisations such as the US Food and Drug Administration (FDA) and the UK Medicines and Healthcare products Regulatory Agency (MHRA). RESULTS: We found 20 systematic reviews, RCTs, or observational studies that met our inclusion criteria. We performed a GRADE evaluation of the quality of evidence for interventions. CONCLUSIONS: In this systematic review we present information relating to the effectiveness and safety of the following interventions: alpha and beta hydroxyl acids, carbon dioxide laser, chemical peel, dermabrasion, facelifts, isotretinoin, natural cartilage polysaccharides (oral or topical), retinyl esters, sunscreens, tazarotene, tretinoin, variable pulse erbium:YAG laser, and vitamin C or E (topical).